Electronic nose for toxic gas detection based on photostimulated core-shell nanowires - Chatchawal Wongchoosuk (2018)
A novel fabrication of microelectronic nose based on ZnO nanowires and ZnO surface modifications including ZnO-ZnAl2O4 core-shell nanowires and ZnO-Zn2TiO4 core-shell nanowires gas-sensing elements operated at room temperature is reported. By combining vapor-phase transport processes and atomic layer deposition techniques, highly homogeneous core-shell nanowires structures can be successfully obtained on large scale areas. Under ultraviolet illumination of the specific oxide surfaces, photo-stimulated oxygen species (O2-(ads)) respond to and dominate the gas sensing mechanism of the core-shell nanowires at room temperature. Principal component analysis results show the perfect discrimination of gases including toxic gases and non-toxic gases. This novel device can be used to identify both gas types with concentrations in the ppb level at room temperature. © 2014 the Partner Organisations.